Integrated chip-size antennas for wireless microsystems : fabrication and design Considerations - Mendes, P. M. (2006)
This paper reports on fabrication and design considerations of an integrated folded shorted-patch chip-size antenna for applications in short-range wireless microsystems and operating inside the 5–6 GHz ISM band. Antenna fabrication is based on wafer-level chip-scale packaging (WLCSP) techniques and consists of two adhesively bonded glass wafers with patterned metallization and through-wafer electrical interconnects. Via formation in glass substrates is identified as the key fabrication step. Various options for via formation are compared and from these, a 193 nm excimer laser ablation is selected for fabrication of the antenna demonstrator. The fabricated antenna has dimensions of 4 mm × 4 mm × 1 mm, measured operating frequency of 5.05 GHz with a bandwidth of 200 MHz at the return loss of −10 dB and a simulated radiation efficiency of 60% were achieved.